2022
DOI: 10.1177/03000605221078785
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of a single-tube PCR and reverse dot blot assay for detection of common α-thalassaemia and β-thalassaemia in Chinese

Abstract: Objective To evaluate a novel reverse dot blot assay for the simultaneous detection six types of common α-thalassaemia alleles (three deletional and three common non-deletional mutations) and 19 types of common β-thalassaemia alleles in a Chinese population. Methods Genomic DNA samples were collected from three hospitals in southern China. The novel thalassaemia gene assay involved one multiplex polymerase chain reaction amplification system and one round of hybridization. Each of the clinically validated DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Frontiers in Genetics frontiersin.org -α 3.7 , -α 4.2 , α WS , and α CS , with allele frequencies of 19.54%, 7.47%, 3.56%, and 3.30%, respectively ( Frontiers in Genetics frontiersin.org more than 2% were −29 (A>G), CD27-28 (+C), CD26 (Hb E) (G>A), IVS-I-1 (G>T), CD43 (G>T), CD14-15 (+G), and Cap (Table 5). Furthermore, a small number of cases suspected with rare genotypes were referred to undergo gene sequencing or gap-PCR (Liang et al, 2022). Rare thalassemia genotypes were identified in 19 cases which were not included in our detection kit; they included four types of rare α-globin genotypes of αα/--THAI (two cases), HKαα/--SEA (four cases), α WS α CD74 GAC>CAC /-α 4.2 (two cases), and α CD31 AGG>AAG α/--SEA (one case).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Frontiers in Genetics frontiersin.org -α 3.7 , -α 4.2 , α WS , and α CS , with allele frequencies of 19.54%, 7.47%, 3.56%, and 3.30%, respectively ( Frontiers in Genetics frontiersin.org more than 2% were −29 (A>G), CD27-28 (+C), CD26 (Hb E) (G>A), IVS-I-1 (G>T), CD43 (G>T), CD14-15 (+G), and Cap (Table 5). Furthermore, a small number of cases suspected with rare genotypes were referred to undergo gene sequencing or gap-PCR (Liang et al, 2022). Rare thalassemia genotypes were identified in 19 cases which were not included in our detection kit; they included four types of rare α-globin genotypes of αα/--THAI (two cases), HKαα/--SEA (four cases), α WS α CD74 GAC>CAC /-α 4.2 (two cases), and α CD31 AGG>AAG α/--SEA (one case).…”
Section: Discussionmentioning
confidence: 99%
“…Thalassemia is prevalent in Middle East, Mediterranean countries, Central Asia, India, and southern China, as well as countries along the north coast of Africa and in South America; about 5% of the world's population is a carrier of thalassemia (Weatherall, 1981;Weatherall, 1997;Lai et al, 2017). Previous studies indicated that there was a high frequency of thalassemia cases in southern China, especially in Guangxi, Guangdong, Jiangxi, and Hainan provinces (Xu et al, 2004;Xiong et al, 2010;Lin et al, 2014;Yao et al, 2014;Yin et al, 2014;Lai et al, 2017;Liang et al, 2022). Patients of each ethnic population carry their own specific types of mutations, including a few very common ones and a variable number of rare ones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the development of highly automated and informatized laboratories, most cumbersome methods have been gradually eliminated. At present, there are many fully automatic methods that are widely used in clinics, but the requirements for clinical laboratories are high, and the machines are expensive [ 18 ]. Moreover, these instruments are used for incidental detection of EFT, which has poor specificity and is not suitable for the preliminary screening of thalassemia in economically underdeveloped areas and grassroots hospitals.…”
Section: Discussionmentioning
confidence: 99%